Antihypercholesterolemic Activity of Tahongai Leaf infusion (Kleinsovia hospita L.) In Mice (Mus musculus L.) - Sianturi, Sister; Sinaga, Clara Ritawany; Leswana, Nurillahi Febria; Butar-Butar, Maria Elvina Tresia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Tahongai (Kleinhovia hospita L.) is an indigenous plant of East Kalimantan known for its health benefits, including antibacterial, anti-inflammatory, antioxidant, anticancer, and antidiabetic properties. This study evaluates the antihypercholesterolemic activity of Tahongai leaf infusion in hypercholesterolemic mice (Mus musculus L.), induced by egg yolk. The test groups included a positive control (simvastatin), a negative control (distilled water), and three treatment groups with Tahongai leaf infusion at concentrations of 15%, 30%, and 60%. The results indicated that the highest reduction in cholesterol levels was observed in the P1 group (15% infusion) with an average decrease of 30.84%, followed by P2 (30% infusion) at 24.79%, and P3 (60% infusion) at 9.31%. The positive control group showed an average reduction of 8.64%. Statistical analysis using One-Way ANOVA revealed a significant difference (p<0.05) in cholesterol level reduction among the treatment groups.